2020
DOI: 10.1002/cb.1831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived value on casual mobile game loyalty: The moderating effect of intensity of playing

Abstract: The retention rate of mobile game players is one of the subjects that spark most interest in the industry, as many abandon the games only a few hours after downloading them. This study examines the antecedents of loyalty towards mobile games from the perspective of perceived value and explores the moderating effect of intensity of playing. The results revealed that hedonic value (i.e., perceived enjoyment and perceived attractiveness) and, to a lesser extent, utilitarian value (i.e., effort expectancy and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 95 publications
2
30
1
Order By: Relevance
“…Third, we explore the formation mechanism of oppositional loyalty to provide a new perspective on how to inspire members' oppositional loyalty towards their community. Previous studies on loyalty have indicated that both hedonic value and utilitarian value can produce loyalty (Abuljadail & Ha, 2019;Molinillo et al, 2020;Sangkoy & Tielung, 2015), but our study shows that only hedonic value is the key cause of oppositional loyalty. Fourth, this article comprehensively surveys several types of online communities, generalizing the findings on oppositional loyalty.…”
Section: Theoretical Implicationscontrasting
confidence: 82%
See 1 more Smart Citation
“…Third, we explore the formation mechanism of oppositional loyalty to provide a new perspective on how to inspire members' oppositional loyalty towards their community. Previous studies on loyalty have indicated that both hedonic value and utilitarian value can produce loyalty (Abuljadail & Ha, 2019;Molinillo et al, 2020;Sangkoy & Tielung, 2015), but our study shows that only hedonic value is the key cause of oppositional loyalty. Fourth, this article comprehensively surveys several types of online communities, generalizing the findings on oppositional loyalty.…”
Section: Theoretical Implicationscontrasting
confidence: 82%
“…Moreover, previous research has associated value with loyalty. Molinillo et al (2020) demonstrated that hedonic value and utilitarian value are crucial in building loyalty. Abuljadail and Ha (2019) pointed out that utilitarian content directly drives brand loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, e-tailers have focused on making products or services accessible to e-shoppers in real time (Qian et al, 2014;Akram et al, 2017). Essentially, e-shopper assertion, contentment and In line with empirical literature (Rajab et al, 2016;Fazal-e-hasan et al, 2018;Lin et al, 2020;Molinillo et al, 2020), PVrecP had a strong positive link with E-Loy (H1). Impliedly, the substantial positive PVrecP-E-Loy relationship signified that E-Loy was possible due to PVrecP.…”
Section: Summary Of Resultsmentioning
confidence: 68%
“…The relationship between hedonic/utilitarian value and satisfaction has been shown to be moderated by a wide range of factors including demographic characteristics (Mosquera, Juaneda-Ayensa, Olarte-Pascual, and Pelegrín-Borondo (2018), product involvement (Lee & Kim, 2018), personality (Moon, 2016), and intensity of game playing (Molinillo, Japutra, and Liébana-Cabanillas (2020). In the current study, we propose a student's year in school may moderate how hedonic and utilitarian values impact student satisfaction.…”
Section: Research Hypothesesmentioning
confidence: 78%